POLITICAL CULTURE AND DEMOCRATIZATION IN RUSSIA - Vijay Kumar (Сравнительная политика, 2015)
On the basis of forty five days field survey as well as extensive survey of literature regarding political culture and democratization process in Russia this paper makes positive case for Russian democratization process, simultaneously this paper is also of the view that the simplistic account of Russian culture can neither help to understand the kind of political culture present in Russia nor its impact on Russian democratization process in particular and prospect of democracy in Russia in general.